LANGMUIR–BLODGETT FILMS AND MOLECULAR ELECTRONICS - HUSSAIN, SYED-ARSHAD; BHATTACHARJEE, D. (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2009)
Molecular electronics is a new, exciting and interdisciplinary field of research. The main concern of the subject is to exploit the organic materials in electronic and optoelectronic devices. On the other hand, the Langmuir–Blodgett (LB) film deposition technique is one of the best among few methods used to manipulate materials at the molecular level. In this article, the LB film preparation technique is discussed briefly with an emphasis on its application towards molecular electronics.